PENGARUH KOMITMEN ORGANISASI, MOTIVASI APARATUR DAN SISTEM PELAPORAN TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA (Studi Pada Pemerintah Kampung di Kecamatan Seruway) - Wahjaharani, Putri; Muhammad Rizqi Zati; Tuti Meutia (Jurnal Mahasiswa Akuntansi Samudra, 2023)
This research aims to determine the influence of organizational commitment, apparatus motivation and reporting systems on the accountability of village fund management in Seruway District. The sample in this study consisted of 60 respondents. The data analysis method uses multiple linear regression analysis, t test, F test, and coefficient of determination test. The regression equation in this study is Y = 4.117 + 0.291X1 + 0.165 X2 + 0.498X3. Organizational commitment, apparatus motivation and the reporting system simultaneously have a positive and significant effect on the accountability of village fund management in the village government in Seruway District. From the coefficient of determination test, it can be explained that the variables of organizational commitment, apparatus motivation and reporting system influence the accountability of village fund management in the village government in Seruway District by 51.5%, while the remaining 48.5% is influenced by other variables outside this research model.